Motivation-Related Goals In Learning English - Islam Assasaki, Bayu (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
This study tries to explore differences in motivation goals in learning English as a foreign language by employing qualitative research. The data were obtained through interviews, observation, and documentation. The results of the interviews showed that English learners deal with different motivations for learning English, both internal and external motivations. However, there is a significant correlation between motivation and learning achievement but the correlation is in the low category. On the basis of this motivation, a strong enthusiasm emerged in mastering English in achieving its target goals. Inseparably from the role of English as the world's language of instruction, English is needed in various aspects of life such as getting a job, scholarships, career advancement, and English behavior.